PENGARUH SIKAP WAJIB PAJAK DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI KECAMATAN SERPONG TANGERANG SELATAN - Fiatri, Lisa Arisa; Manihuruk, Dewi Natasya (Jurnal Ilmu Administrasi Publik, 2025)
This research aims to examine the influence of taxpayer attitudes and the quality of tax services on taxpayer compliance in paying rural and urban land and building taxes in Serpong District, South Tangerang. The study involved 100 respondents, utilizing a quantitative descriptive approach with data collected through questionnaires. The findings indicate that taxpayer attitudes significantly affect compliance, accounting for 46.9% of the variance, while the quality of tax services contributes 37.7%. Overall, these factors explain 61.2% of the variance in taxpayer compliance, highlighting the importance of improving both taxpayer education and service quality to enhance compliance rates.